The wonder of their voices : the 1946 Holocaust interviews of David Boder - Rosen, Alan Charles (The Oxford oral history series, 2013)
Introduction: Boder's happy idea -- I could not help wondering : on Boder's biography and the idea of testimony -- Summer, 1946, pt. 1 : the European expedition and the ethnography of testimony -- Summer, 1946, pt. 2 : the expansion of testimony -- From listening to reading : publishing the interviews -- The wonder of their voices : testimony, technology, and wire recorded narratives -- Making a study of these things : Boder's interviews in the context of psychology -- In divergent tongues and dialects : multilingual interviews and literary experiments -- Epilogue: Rewriting the history of Holocaust testimony -- Appendix 1: Chronology of interviews: July 29-October 4, 1946 -- Appendix 2: The disputed number of Boder interviews -- Appendix 3: Topical autobiographies of displaced people: volumes I through XVI